The formation of postcolonial theory - Rukundwa, Lazare S. (HTS teologiese studies, 2007)
The purpose of this article is to outline certain options and struggles, which gave rise to postcolonial theory. The author deals with various experiences of anti-slavery and anti-colonial movements in Western and tricontinental countries, comprising the development of postcolonial theory. It is argued that postcolonial theory provides a means of defiance by which any exploitative and discriminative practices, regardless of time and space, can be challenged. The article consists of a section in which terminology is clarified, secondly a discussion of the elements that functioned as justification of the formation of postcolonial theory, namely a humanitarian, economic, political, and religious justification. The role of feminism and anti-colonialism is discussed in the third instance, followed by a reflection on the concept “hybrid identities”.